2013
DOI: 10.5296/jbls.v4i2.3195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Amino Acids on Biofilm Growth, Swimming Motility and Twitching Motility in Escherichia Coli BL21

Abstract: Biofilms are surface-attached, matrix-enclosed microbial communities that can cause various diseases like formation of dental plague, urinary tract infection and cystic fibrosis. The purpose of this study was to examine the effects of amino acids (arginine, valine, leucine, glycine, lysine, phenylalanine, threonine and proline) on biofilm formation swimming motility and twitching motility in Escherichia coli BL21. M63 minimal salt media (supplemented with different types and concentrations of amino acids) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
1
22
2
Order By: Relevance
“…Magnification at 60 Â 1.2 NA in DCS1 and 100 Â in DCS3 and DCS5, respectively. of SQR9 to form biofilms in the presence of lysine, histidine, arginine, alanine, cysteine, phenylalanine, methionine, leucine, valine, and isoleucine concurred with other findings where arginine, valine, leucine, lysine, and phenylalanine acted as biofilm promoters in Escherichia coli BL21 and Pseudomonas aeruginosa [29,30]. In other studies, alanine and asparagine were reported as carbon sources for growth mainly by bacteria from the root tips, and to a lesser extent from the intermediate region, of cucumber grown on rock wool [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Magnification at 60 Â 1.2 NA in DCS1 and 100 Â in DCS3 and DCS5, respectively. of SQR9 to form biofilms in the presence of lysine, histidine, arginine, alanine, cysteine, phenylalanine, methionine, leucine, valine, and isoleucine concurred with other findings where arginine, valine, leucine, lysine, and phenylalanine acted as biofilm promoters in Escherichia coli BL21 and Pseudomonas aeruginosa [29,30]. In other studies, alanine and asparagine were reported as carbon sources for growth mainly by bacteria from the root tips, and to a lesser extent from the intermediate region, of cucumber grown on rock wool [31].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, glycine, threonine, serine, glutamate, and aspartate inhibited biofilm formation. Other studies had shown glycine and threonine as having an inhibitory effect on biofilm formation of E. coli BL21 [29].…”
Section: Discussionmentioning
confidence: 91%
“…Histidine and Aromatic Amino Acids Metabolism During Pellicle Biogenesis-Amino acids availability can also modulate bacterial biofilm development (27,68,69). Several proteins involved in the aromatic amino acids metabolism were here found accumulated in pellicles.…”
Section: Increase Of Drug Resistance and Stress Adaptation Proteins Bmentioning
confidence: 80%
“…In Escherichia coli BL21, l‐ lys and l‐ phe (out of eight tested amino acids) have negative effects on motility and biofilm formation (Goh et al . ). In P. aeruginosa ATCC 27853, the addition of l‐ trp and l‐ tyr inhibited biofilm formation, while l‐ met and l‐ leu did not (Brandenburg et al .…”
Section: Discussionmentioning
confidence: 97%